Eufemisme dan Disfemisme dalam “Surat Terbuka Kepada DPR-RI” Narasi TV: Tinjauan Semantik - Icha Fadhilasari; Gita Rosarum Ningtyas (Jurnal Bahasa dan Sastra, 2021)
Euphemisms and dysfemisms are often used as journalism rhetoric for public broadcast/content. This cannot be separated from the role of the mass media as an information institution for all segments. In that case, euphemisms and dysfemisms become expressions to offend and overthrow certain parties deemed to be detrimental to society. This research is motivated by the dominant use of euphemisms and dysfemisms in the video entitled "Dear Sirs and Puan Members of the DPR". This research uses descriptive qualitative method with Keith Allan and Kate Burridge's semantic approach. The research objective is to describe the form, meaning and function of euphemism and dysfemism expressions in the content containing the satire. Sources of research data were taken from social media accounts in the form of Instagram (@najwashihab) and Youtube channel (Narasi TV). The research data were in the form of words and phrases spoken by Najwa Shihab. Data collection used the observation and note technique. The results of this study indicate that Shihab as the narrator uses the dominant form of expression of dysphemism compared to euphemism. So it can be concluded that this broadcast has given the DPR RI a bad image as the target object. Of course, the negative appreciation leads to the performance of the parliament which is considered disappointing or unacceptable to public expectations. In the situation of the Covid-19 pandemic, legislators are aggressively issuing public policies that seem to be impartial to the people, such as the Omnibus Law-Ciptaker Bill, the Criminal Code Bill, the Correctional Bill and so on.